Checklist of Orchidaceae From Brazilian Amazon Restingas - Deivid Lucas de Lima da Costa; Felipe Fajardo Villela Antolin Barberena (New Zealand Journal of Botany, 2026)
In Brazil, restingas (coastal sandbank vegetation) are distributed along the coast in the Atlantic Forest, Caatinga, Cerrado, and Amazon phytogeographic domains. Orchidaceae is one of the botanical families with the greatest species richness in restingas in the Atlantic Forest but has been poorly documented in Amazonian restingas , resulting in limited knowledge in these environments. Thus, the aim of this study was to present a checklist of Orchidaceae from Brazilian Amazon restingas . We consulted herbaria, reviewed the literature, and carried out field collections on the coast of the Salgado microregion in the state of Pará. Twelve genera and 20 species of Orchidaceae were found. Two species are endemic to Brazil, and nine are new records for the study area. Orchidaceae occur in four phytophysiognomies: restinga forest (10 species, five exclusive), open thicket formation (8 spp.), dune field (7 spp., three exclusive), and herbaceous marsh (2 spp.). Eleven species were exclusively terrestrial, six exclusively epiphytes, two epiphytes and terrestrial, and one species was a nomadic climber. Future studies should investigate the ecological relationships between epiphytic orchids and their phorophytes in Amazonian restingas because these relationships have shown to be fundamental in restingas in the Atlantic Forest.